Seroprevalence of EV-A71 neutralizing antibodies following the 2011 epidemic in HCMC, Vietnam. - Fang-Lin Kuo; Truong Huu Khanh; Wan-Yu Chung; Nguyen Thanh Hung; Shu-Ting Luo; Wen-Chiung Chang; Le Nguyen Thanh Nhan; Le Quoc Thinh; Min-Shi Lee (Public Library of Science (PLoS), 2020)
Enterovirus-A71 (EV-A71) cyclically causes hand-foot-mouth disease (HFMD) epidemics in Asian children. An EV-A71 epidemic occurred in Southern Vietnam in 2011, but its scale is not clear. We collected residual sera from non-HFMD Vietnamese inpatients in 2012-2013 to determine seroprevalence of EV-A71 neutralizing antibodies, and measured cross-reactive neutralizing antibody titers against three EV-A71 genogroups. About 23.5% of 1-year-old children in Southern Vietnam has been infected by EV-A71, and the median age of infection was estimated to be 3 years. No significant antigenic variation could be detected among the three EV-A71 genogroups. The high seroprevalence of EV-A71 neutralizing antibody in children living in southern Vietnam indicates the necessity of introducing EV-A71 vaccines in southern Vietnam, particularly for children under 6 months of age. Moreover, it is critical to understand EV-A71 disease burden for formulating national vaccination policy.